2018
DOI: 10.3390/vision2020019
|View full text |Cite
|
Sign up to set email alerts
|

Image Stabilization in Central Vision Loss: The Horizontal Vestibulo-Ocular Reflex

Abstract: For patients with central vision loss and controls with normal vision, we examined the horizontal vestibulo-ocular reflex (VOR) in complete darkness and in the light when enhanced by vision (VVOR). We expected that the visual-vestibular interaction during VVOR would produce an asymmetry in the gain due to the location of the preferred retinal locus (PRL) of the patients. In the dark, we hypothesized that the VOR would not be affected by the loss of central vision. Nine patients (ages 67 to 92 years) and 17 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…We also found that the eyes of the patients do not return to primary position in the dark which means that the central nervous system maintains the eye rotation that allows for eccentric viewing (i.e., the PRL) even when scotomata cannot impair vision. This effect was also found in the VOR data collected from the same patients [28] and is congruent with data reported by White and Bedell [9] in a study of the oculomotor reference of people with bilateral macular disease who tend to report looking "straight ahead" when using the PRL-in other words, during eccentric viewing-reflecting permanent changes in the oculomotor reference. Consistent with this, we found a small indication that eye position control in the dark is related to the patient's eye position control in the light.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also found that the eyes of the patients do not return to primary position in the dark which means that the central nervous system maintains the eye rotation that allows for eccentric viewing (i.e., the PRL) even when scotomata cannot impair vision. This effect was also found in the VOR data collected from the same patients [28] and is congruent with data reported by White and Bedell [9] in a study of the oculomotor reference of people with bilateral macular disease who tend to report looking "straight ahead" when using the PRL-in other words, during eccentric viewing-reflecting permanent changes in the oculomotor reference. Consistent with this, we found a small indication that eye position control in the dark is related to the patient's eye position control in the light.…”
Section: Discussionsupporting
confidence: 91%
“…The data presented here were collected along with those in an already published study of the active horizontal vestibulo-ocular reflex (VOR) of patients with AMD and controls performed at a frequency of 0.5 Hz [28]. The VOR is an image stabilization reflex that minimizes the motion of a target on the retina during head movement by producing compensatory eye movements in the direction opposite to those of the head.…”
Section: Introductionmentioning
confidence: 99%